2021
DOI: 10.1021/acsami.1c08785
|View full text |Cite
|
Sign up to set email alerts
|

Immune Effect Regulated by the Chain Length: Interaction between Immune Cell Surface Receptors and Synthetic Glycopolymers

Abstract: Glycopolymer-based drugs for immunotherapy have attracted increasing attention because the affinity between glycans and proteins plays an important role in immune responses. Previous studies indicate that the polymer chain length influences the affinity. In the studies on enhancing the immune response by glycans, it is found that both oligosaccharides and long-chain glycopolymers work well. However, there is a lack of systematic studies on the immune enhancement effect and the binding ability of oligomers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Matured dendritic cells (DCs) can activate initial T cells and eventually lead to the killing of cancer cells. Many glyco-receptors are expressed on immature DCs, and previous studies have shown that it is possible to use glycopolymers to promote the maturation of DCs . Glycopolymer-modified cancer cells, in addition to changing the migratory behavior, are expected to interact with dendritic cells (DCs) and promote the maturation of DCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matured dendritic cells (DCs) can activate initial T cells and eventually lead to the killing of cancer cells. Many glyco-receptors are expressed on immature DCs, and previous studies have shown that it is possible to use glycopolymers to promote the maturation of DCs . Glycopolymer-modified cancer cells, in addition to changing the migratory behavior, are expected to interact with dendritic cells (DCs) and promote the maturation of DCs.…”
Section: Resultsmentioning
confidence: 99%
“…Many glyco-receptors are expressed on immature DCs, 19 and previous studies have shown that it is possible to use glycopolymers to promote the maturation of DCs. 32 Glycopolymer-modified cancer cells, in addition to changing the migratory behavior, are expected to interact with dendritic cells (DCs) and promote the maturation of DCs. Here we investigate the stimulating effect of glycopolymer-modified B16 cells on the maturation of primary DCs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Their findings indicate that longer macromolecular chains do not always lead to better binding for designing glycopolymers for immune-related proteins. 69…”
Section: Structural Effects On Lectin–glycopolymer Interactionsmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2022 sugar-based adjuvants for immunotherapy, 34,35 and the intelligent drug delivery by pH-responsive polymers and photolysis. 36 Of course, the cytotoxicity of the micromotors also needs to be considered in applications.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…More importantly, the directional motion of the complexes can be made by applying a non-uniform UV light field at a high packing fraction. With their motion capability, polymer-by-design ability, and pH-changing property, the glyco-micromotors demonstrated extensive application potential, for example, in the isolation of biological targets from mixtures, 29,30 the neutralization of toxins, 31–33 the transportation of sugar-based adjuvants for immunotherapy, 34,35 and the intelligent drug delivery by pH-responsive polymers and photolysis. 36 Of course, the cytotoxicity of the micromotors also needs to be considered in applications.…”
mentioning
confidence: 99%